Integrasi SDGs dalam Pengembangan Karakter Generasi Muda di Era Digital - Winandar, Andre (Indonesian Character Journal, 2025)
In the digital age, the main issue in character development is how to empower young people who have the principles of social responsibility, equality, and sustainability amidst the challenging influence of modern technology. The purpose of this research is to explore how the Sustainable Development Goals (SDGs) can serve as a basis for character education and to find challenges and opportunities in its integration in the digital era. The approach used in this research is qualitative descriptive with a literature study method. The results show that through the values of sustainability and equality, the SDGs provide a framework for developing student character supported by digital technology. Some of the challenges that need to be overcome include the digital divide, the negative influence of technology, and cultural constraints. On the other hand, great opportunities are also found in the use of technology to expand access to quality character education. Therefore, the integration of the SDGs in character education requires strategies that involve multi-stakeholder collaboration as well as customization to the local context.